Dakwah sebagai Pendorong Pembangunan Ekonomi Berkelanjutan di Masyarakat - Ansori, Teguh (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to understand the relationship between da'wah and economic development, the basic concept of development, and sustainable economic development. Currently, da'wah is often seen only as an activity to spread religious teachings, not as an effort to improve people's welfare, even though there are still inequalities in development, especially in the economic aspect. The method used in this study is Library Research, which utilizes various literature to collect data from relevant sources, such as journals, books, books, and certain writings. In the perspective of Islam, da'wah is not only limited to ritual and spiritual aspects, but also covers various aspects of life, including economics. Islam emphasizes that the well-being of society involves more than just worship of Allah; It is also related to how individuals and communities can live decently, prosperously, and fairly. Da'wah and economic development influence each other and can strengthen each other. In addition, education and the dissemination of religious values play an important role in increasing public awareness and knowledge. Development aims to improve the standard of living of the community to be better and prosperous, it is expected to meet the economic, social, and environmental needs of the current community without sacrificing the capabilities of future generations